The dental management of a patient with hyperimmunoglobulinemia E syndrome: a case report - N. J. MCAULIFFE, M. L. HUNTER, C. H. KAU, B. HUNTER & J. KNOX (Paediatric Dentistry, 2005)
First described prior to the discovery of immunoglobulin E (IgE), the hyperimmunoglobulinemia E syndrome (HIES) was originally called Job’s syndrome on account of the cutaneous ‘cold abscesses’ which were observed in this condition [2].